Enriquecimento nutricional de pão de forma com concentrado protéico de soro de leite e carbonato de cálcio - Oliveira, Naara Medeiros Araujo Lima (2010)
The aim of this work was to enrich tin loaf with 7,5% of whey protean concentrate (WPC) and calcium carbonate in concentrations of 1,5%, 2,0% and 2,5% developing a final product with more concentration of proteins and minerals, especially calcium. Yet, conventional tin loaf was prepared by ways of comparison. The loaves were evaluated in relation to sensorial acceptance and were submitted to analysis of pH, acidity and specific volume. The pH and acidity of fresh dough were also analyzed. These analysis were carried out in third copy with five repetitions. Out of the tested formulations only one was selected based in results of physical chemical and sensorial tests. The proteins, lipids, ashes, chlorides and calcium concentrations were determinated only in selected formulation and in conventional product, in third copy, with three repetitions. Acidity reduction and pH increase were checked in fresh dough, probably due to the addition of calcium carbonate, however, these modifications did not result in volume reduction of the loaves. In the sensorial test, the formulation F2 presented the best acceptance, being for that reason selected. In the chemical composition analysis it was checked that the addition of whey protean concentrate and calcium carbonate to the tin loaf formulation, resulted in a final product with greater nutritional value as compared to conventional bread, especially in terms of proteins and calcium. In the case of calcium, the increment was sufficient to supply around 70% of the DRI for adults. Tin loaf enrichment with WPC and calcium carbonate establish as an important alternative in the elevation of calcium consumption, especially for the good acceptance and low cost of the product as compared to milk and derivatives, which are the main sources of this mineral.